A retrospective study comparing treatment outcomes of spontaneous healing, scaffolding with silastic sheet and gelfoam in patients with traumatic tympanic membrane perforations - Patel, Monika; Kaushik, Maitri; Dehadaray, Arun; Gaikwad, Viraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Objective of the study was to compare the treatment outcome of conservative management, intervention with silastic sheet and gelfoam mixed with autologous blood in traumatic perforations of tympanic membrane. Methods: A retrospective study was conducted on 69 patients; with traumatic ear perforation were treated by conservative management, silastic sheet placement and gelfoam with autologous blood. Patients data every week and minimum of 4 visits was documented. On follow up data was reassessed in terms of symptom improvement, healing of perforation, duration for healing and development of secondary infection. Statistical analysis was done using Fischer’s exact test. Results: Out of the 69 patients group1 consisted of 38 patients, group2 had 19 and group3 had 12 patients. The age ranged from 02-72 years, with greater incidence in females. In group 1 though the healing rate was very good symptom improvement was gradual. The symptom improvement in both group 2 and 3 were satisfactory and highly significant p<0.001. The difference in healing outcome of three modality of treatments was found significant p<0.05 but the occurrence of infection and local reaction did not affect the healing outcome at the end p<0.05. Conclusions: Traumatic TM perforations have a high chance of healing. Treatment outcome should not consider only healing status as a sole measure but symptom relief from distressing symptoms like ear buzzing or tinnitus and hearing loss should also be considered. Use of scaffolding method can be useful in such cases. Hence selection of proper treatment modality should be considered based on patient complaints.